2022
DOI: 10.3748/wjg.v28.i8.794
|View full text |Cite
|
Sign up to set email alerts
|

Mixed neuroendocrine–nonneuroendocrine neoplasms of the gastrointestinal system: An update

Abstract: Mixed neuroendocrine-nonneuroendocrine neoplasms (MiNENs) of the digestive tract are a rare heterogeneous group of tumors that present many challenges in terms of diagnosis and treatment. Over the years, the diagnostic criteria, classification, and clinical behavior of these tumors have been the subjects of ongoing debate, and the various changes in their nomenclature have strengthened the challenges associated with MiNENs. This review is performed to provide an understanding of the key factors involved in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 111 publications
0
34
0
Order By: Relevance
“…Multiple biopsies yielded a possible diagnosis of Amp-MiNEN. It has been reported that collecting both component with biopsy or cytology is difficult, and in patients with metastatic disease, biopsies are usually performed from metastases, which are likely to have only one component [ 5 7 ]. In addition, the requirement for 30% ≥ proportions of each of the major components for a definitive diagnosis of MiNEN is controversial [ 5 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple biopsies yielded a possible diagnosis of Amp-MiNEN. It has been reported that collecting both component with biopsy or cytology is difficult, and in patients with metastatic disease, biopsies are usually performed from metastases, which are likely to have only one component [ 5 7 ]. In addition, the requirement for 30% ≥ proportions of each of the major components for a definitive diagnosis of MiNEN is controversial [ 5 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that collecting both component with biopsy or cytology is difficult, and in patients with metastatic disease, biopsies are usually performed from metastases, which are likely to have only one component [ 5 7 ]. In addition, the requirement for 30% ≥ proportions of each of the major components for a definitive diagnosis of MiNEN is controversial [ 5 7 ]. Actually, there have been some reports of mixed tumors that did not meet diagnostic criteria for MiNEN because of this 30% threshold, but can be clinically considered MiNEN [ 8 , 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, it has been reported that diagnosing MiNENs solely by quantifying IHC results can lead to terminological inconsistencies and confusion ( 55 ). Therefore, the WHO makes it very evident that these histological findings must be present in each morphological component and that IHC data alone are insufficient for the diagnosis of MiNENs ( 56 ). Another issue that should be considered is the necessity to give a diagnosis of MINENs in cases that do not receive neoadjuvant therapy.…”
Section: Diagnosis Of Gastric Minensmentioning
confidence: 99%
“…Extensive surgery is not indicated in metastatic disease, especially in high-grade cases. Systemic chemotherapy is advocated in such cases[ 11 ].…”
Section: Diagnosismentioning
confidence: 99%